Alkaline extraction of polyphenols for valorization of industrial spruce bark. (September 2022) - Borrega, Marc; Kalliola, Anna; Määttänen, Marjo; Borisova, Anna S.; Mikkelson, Atte; Tamminen, Tarja
Abstract: Industrial spruce bark is an abundant side-stream from forest industries that contains tannins and other phenolic compounds that can be exploited in a variety of applications. In this study, alkaline extractions of spruce bark conducted under a wide range of process conditions showed that 20–27 % of the bark could be extracted as polyphenols, mainly tannins and some lignin. The polyphenols in alkaline extracts from two selected scale-up extractions, conducted at 100 °C with 15 % NaOH and at 160 °C with 24 % NaOH, were then recovered by acidic precipitation and tested as surfactants. Despite their different composition, the polyphenol-rich precipitates showed similar surface activity than a commercial biosurfactant, and were also soluble under neutral conditions. Moreover, sugar yields above 80 % could be obtained by enzymatic saccharification of the extracted bark residues. These results demonstrated that alkaline extraction is a promising technology for valorization of industrial bark side-streams. Graphical abstract: Unlabelled Image Highlights: About 25 % of spruce bark is extracted as polyphenols by alkaline extraction. Extracted polyphenols show surface activity similar to a commercial biosurfactant. Above 80 % of the sugar fraction in extracted bark can be enzymatically hydrolyzed. Alkaline extraction is an effective technology to valorize industrial bark streams.